Single‐phase All‐solid‐state Silver Battery using Ag1.5Cr0.5Ti1.5(PO4)3 as Anode, Cathode, and Electrolyte. Issue 34 (13th September 2018) - Inoishi, Atsushi; Nishio, Akira; Kitajou, Ayuko; Okada, Shigeto
Abstract: An all‐solid‐state silver battery made from a single material is reported. NASICON‐type Ag1.5 Cr0.5 Ti1.5 (PO4 )3 functioned as the anode, cathode, and electrolyte. High rate capability at 298 K and low temperature operation (233 K) were possible due to its high electrical conductivity and low interfacial resistance with the concept of a single‐phase battery. The redox reactions of Ag/Ag + (anode) and Cr 3+ /Cr 4+ (cathode) were confirmed from X‐ray diffraction and X‐ray photoelectron spectroscopy measurements. The operating voltage of the battery in this study was higher than that for a silver battery using an AgI solid electrolyte because of the high redox potential of the cathode and the wider potential window of Ag1.5 Cr0.5 Ti1.5 (PO4 )3 than that of AgI. Therefore, Ag1.5 Cr0.5 Ti1.5 (PO4 )3 ‐based single‐phase battery is a promising new concept to obtain a high voltage silver‐ion battery, high‐rate capability and low temperature operation. Abstract : Herein, we report a single‐phase all‐solid‐state battery made from a single material (Ag1.5 Cr0.5 Ti1.5 (PO4 )3 ). The new concept performed the low resistance of the cell and higher cell voltage than typical silver battery.